2014
DOI: 10.1007/978-3-319-12048-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy of Glioblastoma

Abstract: Glioblastoma multiforme (GBM) is the most common malignant brain tumor that affects approximately 17,000 patients annually. Clear survival advantages have been demonstrated with postoperative radiation therapy (RT) to doses of 5,000-6,000 cGy but dose-escalation attempts beyond 6,000 cGy have resulted in increased toxicity but no additional survival benefit. To improve local control and limit toxicity to normal brain tissue with these infiltrating tumors, novel imaging techniques are actively being explored to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 98 publications
(102 reference statements)
1
67
0
2
Order By: Relevance
“…IFRT delivers external beam RT to the tumor with a 2–3 cm margin, which is based on the observation that, following RT, GBM recurs within 2 cm of the original tumor site in 80%–90% of cases (Narayana et al, 2006). Multiple studies in the early 1970s confirmed that IFRT had similar or slightly improved survival advantage over WBRT, with less normal tissue damage within the RT field (Barani & Larson, 2015). …”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…IFRT delivers external beam RT to the tumor with a 2–3 cm margin, which is based on the observation that, following RT, GBM recurs within 2 cm of the original tumor site in 80%–90% of cases (Narayana et al, 2006). Multiple studies in the early 1970s confirmed that IFRT had similar or slightly improved survival advantage over WBRT, with less normal tissue damage within the RT field (Barani & Larson, 2015). …”
Section: Treatmentmentioning
confidence: 99%
“…The typical total dose delivered is 60 Gy, in 1.8–2 Gy fractions administered five days per week for six weeks. A clear survival advantage has been demonstrated with postoperative RT doses to 60 Gy, but dose escalation beyond this has resulted in increased toxicity without additional survival benefits (Barani & Larson, 2015). …”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Involved field fractionated radiotherapy doubled the overall survival from 6 to 12 months, and became next to surgery a cornerstone of the current standard of care [10]. Many trials focusing on doseescalation, hypo-or hyperfractionation, as well as radiosensitization or delivery of radiation as brachytherapy have not improved survival [12]. Although alkylating chemotherapy has been used for several decades, there was no significant improvement in overall survival until the introduction of temozolomide, which resulted in a 2.5-month increase in median survival [13].…”
Section: Introductionmentioning
confidence: 98%
“…It should be noted that dose-escalation attempts with photons beyond 60 Gy have resulted in increased toxicity but no additional survival benefit. 87 In a Phase II trial, the conventional 55-65 Gy photons dose was escalated to 90 Gy-E with a combination of protons and photons in accelerated fractionation. 88 The treatment led to a central tumour control in most cases, but tumours recurred in the periphery, and median survival time was 20 months.…”
Section: Particle Therapymentioning
confidence: 99%